Effects from consistent internalization of external effects from transport and manufacturing – a CGE analysis for Sweden - Xing Liu; Lars Bohlin (Örebro University School of Business, 2012)
This paper uses a static, small open-economy computable General Equilibrium (CGE) model of the Swedish economy to study the effects of consistent internalization of external effects from transport and manufacturing. We look at eight policy scenarios: first a fully implemented Social Marginal Cost Pricing (SMCP) in manufacturing, sea and air transport, road transport, and rail transport; and then SMCP in these sectors separately or in various combinations. We evaluate effects on, among others, national and global emission reductions, GDP, government budget, and social welfare. The results show that the fully implemented SMCP in all sectors generates the highest social welfare surplus, largest emission reduction and largest government net revenue. When this option is not feasible, society still could benefit from correcting prices in or more sectors. Correcting prices only for rail transport generates very small social welfare surplus, emission reduction and government revenue; while correcting prices only for road transport generates much larger effects in all aspects. Taking into consideration that sea and air modes are regulated not only by domestic legislation, the findings from this study suggest that the second-best policy scenario could be to correct prices for the rail, road and manufacturing sectors.
Keywords: C68; H23; R48; 330; social marginal cost; externalities; transport taxation; CO2 taxation; general equilibrium